Melatonin, mitochondria, and the metabolic syndrome - Cardinali, Daniel Pedro (2017)
Fil: Cardinali, Daniel Pedro. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina